Clubture: The Profile of Organizations and Collaborative Practices - Kardov, Kruno (Array, 2007)
The authors present research findings on financial, human, spatial and technical resources of the independent cultural scene in Croatia, as well as dominant collaborative practices within the cultural sector. One of the most important results of the research show that the Clubture network is dominated by organizations of local character (those that are most active on local level and also that most often choose the partners for collaboration within such spatial frameworks). Furthermore, the data show an uneven geographic distribution of networked organizations, a dominant informal pattern of collaboration, a strong project-programme orientation, domination of small organizations in terms of resources (financial, human and spatial) as well as extensive reliance on voluntary work.